2015
DOI: 10.1590/s0102-6720201500040014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hepatic Profile in Pre and Postoperative of Bariatric Surgery: Private vs Public Network

Abstract: Background: Obesity is associated to several comorbidities, including nonalcoholic fatty liver disease, which implicates in isolated steatosis to steatohepatitis. The latter may progress to severe manifestations such as liver fibrosis, cirrhosis and hepatocellular carcinoma. Aim: To compare the presence of advanced liver fibrosis before and after bariatric surgery in patients of private and public health system. Methods: Patients from public and privative networks were studied before and after bariatric surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Two recent meta-analyses have reported that RYGB had a positive effect on NAFLD after short- to mid-term follow-up time of 1–60 months, with improvement or resolution of histological steatosis and steatohepatitis in the majority of patients, as well as resolution of fibrosis in 28–51% [ 12 , 13 ]. Importantly, studies assessing resolution of liver fibrosis after RYGB with NFS and/or FIB-4 have found improvement in agreement with studies using biopsies [ 26 , 27 , 28 , 29 ]. The proportion of patients with a low postoperative fibrosis score was similar in our population to that in studies with shorter follow-up times [ 11 , 12 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 71%
“…Two recent meta-analyses have reported that RYGB had a positive effect on NAFLD after short- to mid-term follow-up time of 1–60 months, with improvement or resolution of histological steatosis and steatohepatitis in the majority of patients, as well as resolution of fibrosis in 28–51% [ 12 , 13 ]. Importantly, studies assessing resolution of liver fibrosis after RYGB with NFS and/or FIB-4 have found improvement in agreement with studies using biopsies [ 26 , 27 , 28 , 29 ]. The proportion of patients with a low postoperative fibrosis score was similar in our population to that in studies with shorter follow-up times [ 11 , 12 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 71%
“…Resection appears today as the main approach for treatment of HCC, especially in patients with good liver function. This mainly occurs because of the restrictive criteria and the inadequate supply of grafts for transplantation in the world 1 , 11 , 13 , 16 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Nascimento et al analyzed changes in NAFLD Fibrosis Score before and after bariatric surgery. The NAFLD Fibrosis Score changed from −0.6845 before the surgery to −1.6898 12 months after the procedure (p < 0.0002), indicating an absence of advanced liver fibrosis in any patient 12 months after the surgery [35] In the above-mentioned study, a weak negative correlation between the decrease in NAFLD Fibrosis Score and weight loss parameters (%EWL (r = −0.251, p < 0.0001) and %TWL (r = −0.280, p < 0.0001)) was observed [37]. In our study, a statistically significant decrease in NAFLD Fibrosis Score was also seen.…”
Section: Discussionmentioning
confidence: 94%